Tunable MEMS-based meta-absorbers for nondispersive infrared gas sensing applications - Kunye Li; Yuhao Liang; Yuxin Liu; Yu-Sheng Lin (Microsystems & Nanoengineering)
Abstract In conventional nondispersive infrared (NDIR) gas sensors, a wide-spectrum IR source or detector must be combined with a narrowband filter to eliminate the interference of nontarget gases. Therefore, the multiplexed NDIR gas sensor requires multiple pairs of narrowband filters, which is not conducive to miniaturization and integration. Although plasmonic metamaterials or multilayer thin-film structures are widely applied in spectral absorption filters, realizing high-performance, large-area, multiband, and compact filters is rather challenging. In this study, we propose and demonstrate a narrowband meta-absorber based on a planar metal–insulator–metal (MIM) cavity with a metallic ultrathin film atop. Nearly perfect absorption of different wavelengths can be obtained by controlling the thickness of the dielectric spacer. More significantly, the proposed meta-absorber exhibits angle-dependent characteristics. The absorption spectra of different gases can be matched by changing the incident angle of the light source. We also preliminarily investigate the CO2 gas sensing capability of the meta-absorber. Afterward, we propose a tunable meta-absorber integrated with a microelectromechanical system (MEMS)-based electrothermal actuator (ETA). By applying a direct current (DC) bias voltage, the inclination angle of the meta-absorber can be controlled, and the relationship between the inclination angle and the applied voltage can be deduced theoretically. The concept of a tunable MEMS-based meta-absorber offers a new way toward highly integrated, miniaturized and energy-efficient NDIR multigas sensing systems.